As aquarelas de Debret e a construção da Identidade Nacional Brasileira: uma análise das coleções didáticas de História do PNLD 2015 - Freitas, Thayane da Rocha Cruz Dias (2018)
This work aims to analyze the pictures of the French painter Jean-Baptiste Debret present in three didactic collections of the second year of High School History as approved by the National Program of Teaching Books (PNLD) 2014/2015. Debret arrived in Brazil with the French Artistic Mission in 1816 and remained for fifteen years. Debret’s pictures are used until today to reinforce discourses linked to the construction of Brazilian national identity. In the formation of these discourses we find the strong presence of the State through the Brazilian Historical and Geographical Institute that analyzed the watercolors of Debret after the publication of the travelogue of the painter, Voyage pittoresque et historique au Brésil(1834, 1835 e 1839). The IHGB had a pivotal role in the construction of the idea of being Brazilian from the myth of the three races: the black, the indigenous and the Portuguese. In his watercolors, Debret paints daily scenes of the Carioca capital of the nineteenth century, such as slave labor. There was construction of national identity reinforced by History Teaching through textbooks until today. We will analyze how the images of Debret collaborated to build Brazilian national identity and how these images have been used in the teaching of History throughout time and in relation to the discourses associated to the work of Debret.